If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3 + -1(-1g) = -8 Remove parenthesis around (-1g) -3 + -1 * -1g = -8 Multiply -1 * -1 -3 + 1g = -8 Solving -3 + 1g = -8 Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + 1g = -8 + 3 Combine like terms: -3 + 3 = 0 0 + 1g = -8 + 3 1g = -8 + 3 Combine like terms: -8 + 3 = -5 1g = -5 Divide each side by '1'. g = -5 Simplifying g = -5
| w^2=4w+3 | | 3/7w-11=-4/7 | | 8x^9-(6x^9-7)=0 | | 5z^6-(-3z^6-3v)=0 | | 10x-185=4x-11 | | -5x-y=-8 | | -(x-8)=13 | | 18-8+6-18/9 | | (-15b^7-7)-(-2b^7)=0 | | x*x-x*y*y-x+y=0 | | 3x+32=48 | | 3x+32=487 | | x+20/x=-9 | | 4x+7y-12-6x+2y+4= | | 2x+3x+5x=90 | | 4.5/7=19.8/x | | 6f+4b=30 | | 6B+4F=30 | | 2(x-30)=x+5 | | (21x-4)/10=-15 | | 9=10-x | | 9x^2+24x+16-y^2=0 | | -4b=-3b^2+15 | | 4x^(-3/4)*2x^(1/8) | | 20m+6=12m-25 | | a=(b+c)/2 | | 3x^2+5y^2+12x-60y+177=0 | | -5x=-400 | | 3z^2-22=56 | | x-2x-1=2 | | 2x-3x-15=5 | | -2(x-1)+3(2x-2)=-100 |